Experience as cognition: musical sense-making and the ‘in-time/ outside-of-time’ dichotomy - Reybrouck, Mark (Interdisciplinary Studies in Musicology, 2019)
Musical sense-making relies on two distinctive strategies: tracking the moment-to-moment history of the actual unfolding and recollecting actual and previous sounding events in a kind of synoptic overview. Both positions are not opposed but complement each other. The aim of this contribution, therefore, is to provide a comprehensive framework that provides both conceptual and operational tools for coping with the sounds. Five major possibilities are proposed in this regard: (i) the concepts of perspective and resolution, which refer to the distance the listener takes with respect to the sounding music and the fine-grainedness of his/her discriminative abilities; (ii) the continuous/discrete dichotomy which conceives of the music as one continuous flow as against a division in separate and distinct elements; (iii) the in time/outside-of-time distinction, with the former proceeding in real time and the latter proceeding outside of the time of unfolding; (iv) the deictic approach to musical sense-making, which conceives of an act of mental pointing to the music, and (v) the levels of processing, which span a continuum between primitive sensory reactivity to actual sounding stimuli and high-level symbolic processing.